2015
DOI: 10.7598/cst2015.1069
|View full text |Cite
|
Sign up to set email alerts
|

Use of Barium Chromate in Photocatalytic Degradation of Eosin Yellow

Abstract: Environmental pollution is a big problem faced by everyone all over the world, out of which water pollution is a major one. In solving the problem of water pollution, photocatalysis plays an important role. In the present work, barium chromate powder has been used as a photocatalytst to degrade Eosin Yellow. The rate of decomposition was affected by different parameters such as pH, concentration of dye, amount of photocatalyst and intensity of light. The optimum conditions were obtained as pH = 7.5, [Eosin Yel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…This hydroxyl radical will oxidize Hg-picrate, which may ultimately degrade the products. Gupta et al (18) reported that hydroxyl radical take part as an active oxidizing species in the degradation of compounds, and observed that in the presence of hydroxyl radial quencher the reaction was appreciably reduced (19) . These reactions were observed by taking different volumes of alcohols (e.g.…”
Section: Effect Of Radical Quenchermentioning
confidence: 99%
“…This hydroxyl radical will oxidize Hg-picrate, which may ultimately degrade the products. Gupta et al (18) reported that hydroxyl radical take part as an active oxidizing species in the degradation of compounds, and observed that in the presence of hydroxyl radial quencher the reaction was appreciably reduced (19) . These reactions were observed by taking different volumes of alcohols (e.g.…”
Section: Effect Of Radical Quenchermentioning
confidence: 99%
“…The textile industry uses this colorant for these strong coloring properties and its bright color. Eosin Y has a biological degradation once it reaches the environment and can be toxic to insects, also for aquatic life, because of its stability [24,25].…”
Section: Introductionmentioning
confidence: 99%